Recovery of Shoulder Rotational Muscle Strength After Arthroscopic Bankart Repair. Issue 9 (27th September 2017) - Amako, Masatoshi; Arino, Hiroshi; Tsuda, Yoshifumi; Tsuchihara, Toyokazu; Nemoto, Koichi
Background: Shoulder rotational muscles act as dynamic stabilizers of the glenohumeral joint, and the recovery of muscle strength plays an important role in stabilizing the joint during postoperative rehabilitation. However, temporal changes in muscle strength after arthroscopic Bankart repair have not been clarified. Purpose: To better understand the temporal recovery of shoulder rotational muscle strength after arthroscopic Bankart repair. Study Design: Case series; Level of evidence, 4. Methods: Isokinetic concentric shoulder rotational muscle strength was evaluated in 50 patients who were diagnosed with recurrent dislocations of the glenohumeral joint and treated with arthroscopic Bankart repair. Results: The mean peak torque/weight and total work were reduced significantly at 1.5 months after surgery ( P < .0001) and returned to preoperative levels by 6 months for external rotation and 4.5 months for internal rotation. The contralateral peak torque ratios reached preoperative levels by 6 months after surgery. The ipsilateral peak torque ratios were reduced between 1.5 and 3 months after surgery and returned to preoperative levels at 6 months for external rotation and 4.5 months for internal rotation. Conclusion: Isokinetic shoulder rotational muscle strength after arthroscopic Bankart repair recovered to preoperative levels by 6 months for external rotation and 4.5 months for internal rotation.